Asymmetric dihydroxylation route to (R)-(-)-octopamine, (R)-(-)-tembamide and (R)-(-)-aegeline - Sadyandy, R.; Fernandes, R. A.; Kumar, P. (Arkivoc, 2005)
A simple and efficient asymmetric synthesis of (R)-(-)-octopamine 1, (R)-(-)-tembamide 2 and (R)-(-)-aegeline 3 is described for the first time employing the Sharpless asymmetric dihydroxylation (AD) as the source of chirality. (C) 2004 Elsevier Science Ltd. All rights reserved.
Keywords: aegeline; Asymmetric synthesis; Dihydroxylation; octopamine; tembamide

Simple and practical approach to enantiomerically pure (S)-3-hydroxy-gamma-butyrolactone: synthesis of (R)-4-cyano-3-hydroxybutyric acid ethyl ester - Kumar, P.; Deshmukh, A. N.; Upadhyay, R. K.; Gurjar, M. K. (Tetrahedron-Symmetry, 2005)
The oxidation of alpha- or beta-(1,4) linked disaccharides or oligosaccharides with cumene hydroperoxide in the presence of a base gave (S)-3,4-dihydroxybutyic acid, which was cyclized under acidic conditions to furnish (S)-3-hydroxy-gamma-butyrolactone. This was subsequently converted into (R)-cyano-3-hydroxybutyric acid ethyl ester, an intermediate for statin based drugs and other related compounds. (c) 2005 Elsevier Ltd. All rights reserved.

Enantio- and diastereocontrolled total synthesis of (+)-boronolide - Kumar, P.; Naidu, S. V. (Journal of Organic Chemistry, 2006)
An efficient stereoselective total synthesis of (+)-boronolide from valeraldehyde is described. The key steps include a Sharpless asymmetric hydroxylation, a chelation-controlled vinyl Grignard reaction followed by a Sharpless asymmetric epoxidation, hydrolytic kinetic resolution, and a ring-closing metathesis.

Tri-tert-butanolamine as an organic promoter in nucleophilic fluorination - Shinde, Sandip S.; Khonde, Nilesh; Kumar, P. (ChemistrySelect, 2017)
Tri-tert-butanol amine acts as promoter with alkali metal salts in the nucleophilic fluorination of alkylsulfonates. It significantly enhances the reactivity of alkali metal salts with minimum formation of side-products (alkene, ether, and alcohol) com-pared to other catalysts in fluorination reaction. The synergism of tert-alcohol and amine moiety plays a pivotal role in fluorination.

2D layered transition metal dichalcogenides (MoS2): Synthesis, applications and theoretical aspects - Singh, A.K.; Kumar, P.; Late, D.J.; Kumar, A.; Patel, S.; Singh, J. (Applied Materials Today, 2018)
Recently, graphene and other two-dimensional (2D) transition metal dichalcogenides (TMDCs) have been widely explored due to their unique optical, mechanical, electrical and sensing properties for versatile electronic and optoelectronic applications. The atomically thin layers of TMDC materials have shown potential to replace state-of-the-art silicon-based technology. Graphene has already revealed an excess of new physics and multifaceted applications in several areas. Similarly, mono-layers of TMDCs such as molybdenum disulfide (MoS2) have also shown excellent electrical and optical properties possessing a direct band-gap of ∼1.8 eV combined with high mechanical flexibility. In contrast to semi-metallic graphene, the semiconducting behavior of MoS2 allows it to overcome the deficiencies of zero-band-gap graphene. This review summarizes the synthesis of 2D MoS2 by several techniques, i.e., mechanical and chemical exfoliation, RF-sputtering, atomic layer deposition (ALD) and chemical vapor deposition (CVD), etc. Furthermore, extensive studies based on potential applications of MoS2 such as the sensor, solar cells, field emission and as an efficient catalyst for hydrogen generation has been included. Theoretical aspects combined with the experimental observations to provide more insights on the dielectric, optical and topological behavior of MoS2 was highlighted.

Catalytic and efficient synthesis of optically active terminal epoxides and 1,2-diols using a new lanthanum triflate assisted C1-symmetric bimetallic chiral salen cobalt complex - Patel, D.; Thakur, S. S.; Shinde, S. S.; Kumar, P. (Letters in Organic Chemistry, 2018)
The catalytic asymmetric synthesis of terminal epoxides and 1,2-diols via a hydrolytic kinetic resolution of racemic terminal epoxides using a new bimetallic chiral salen CoIII complex incorporated with La(OTf)3 as a catalyst is reported. The new bimetallic chiral salen CoIII complex bearing La(OTf)3 was prepared in a one-pot procedure by activation and bimetallic complex formation from the inactive Jacobsen chiral salen CoII complex (salen = N, N′-bis(3,5-di-tert-butylsalicylidene)-1,2- cyclohexane-diamine). We observed that C1-symmetric chiral bimetallic Co-complex coordinated with La(OTf)3 works as a chiral catalyst and remarkably increased the reactivity and enantioselectivity in the hydrolytic kinetic resolution of terminal epoxides compared to its monometallic analogues. La(OTf)3 plays a crucial role as an achiral Lewis acid in this process, which is supported by the experimental observation presented. To explore the absolute configuration of glycidyl butyrate a vibrational circular dichroism (VCD) spectra was calculated using density functional theory.

Retraction: a highly concise and practical route to clavaminols, sphinganine and (+)-spisulosine via indium mediated allylation of α-hydrazino aldehyde and a theoretical insight into the stereochemical aspects of the reaction - Pandey, M.; Chowdhury, P. S.; Dutta, A. K.; Kumar, P.; Pal, S. (RSC Advances, 2019)
A conceptually different approach has been employed for the synthesis of 1,2-amino alcohols by proline-catalyzed α-amination of aldehyde and one-pot indium mediated allylation of the crude α-hydrazino aldehydes. DFT based quantum chemical calculations have been performed to obtain a quantitative explanation of the stereoselectivity of the reaction.